Determinação do teor alcoólico da cachaça: uma abordagem das propriedades intensivas - Monteiro, Isabel Cristina de Castro [UNESP]; Vaz, Ednilson Luiz Silva [UNESP]; Codaro, Eduardo Norberto [UNESP]; Acciari, Heloísa Andréa [UNESP]; Monteiro, Marco Aurélio Alvarenga [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2012)
The Resolution number 3 of the Câmara de Educação Básica (CEB)/Conselho Nacional de Educação (CNE), published in 1998, June 26 (BRASIL, 1998), which established the National Curriculum Guidelines for High School Education, emphasizes the interdisciplinarity, in its 8th Article. However, almost fourteen years later, the reality in most of our schools is the adoption of a merely disciplinary methodology, vis-à-vis the difficulty related to educational planning activities of this kind. In this paper, we present a proposal of an interdisciplinary experimental activity that addresses the concept of surface tension, connecting physicists and chemists. The idea is that students determine the alcohol content of “cachaça” and discuss the concepts of surface tension forces between equal molecules, similar and different.

A Resolução número 3 da Câmara de Educação Básica (CEB)/Conselho Nacional de Educação (CNE) de 26 de junho de 1998 (BRASIL, 1998), que institui as Diretrizes Curriculares Nacionais para o Ensino Médio, destaca a interdisciplinaridade em seu artigo 8. Contudo, quase 14 anos depois, a realidade na maioria de nossas escolas é a adoção de uma metodologia meramente disciplinar, tendo em vista a dificuldade em se planejar atividades de ensino desse tipo. Nesse trabalho, apresentamos uma proposta de atividade experimental interdisciplinar que permite uma abordagem do conceito de tensão superficial aproximando físicos e químicos. A ideia é que os alunos determinem o teor alcoólico da cachaça e que discutam os conceitos de tensão superficial e das forças existentes entre moléculas iguais, similares e diferentes.
Keywords: Surface content; Cachaça; Interdisciplinarity; Alcoholic content; Tensão superficial; Teor alcoólico; Cachaça